1992
DOI: 10.1111/j.1432-1033.1992.tb16864.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine(5′)hexaphospho(5′)adenosine stimulation of a Ca2+‐induced Ca2+‐release channel from skeletal muscle sarcoplasmic reticulum

Abstract: Stimulation of a Ca2 +-induced Ca2 +-release channel from skeletal muscle sarcoplasmic reticulum by various adenosine(5')oligophospho(5')adenosines (Ap.A, n --2 -6) by a rapid quenching technique using radioactive calcium was studied. Ap4A, Ap5A and Ap6A, as well as adenosine S'-[B,ymethyleneltriphosphate (AdoPP [CH2]P), a non-hydrolyzable ATP analogue, stimulated the Ca2 +-release channel, whereas ApzA and Ap3A had no effect. At a concentration of 0.5 mM, the order of stimulation was AdoPP[CH,]P < Ap4A < Ap,A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…As such large dierences in the activity of the adenine nucleotides can be achieved by the removal or addition of a single phosphate group, electrostatic interactions between the phosphates and the amino acid residues in the binding sites may play an important role in determining the ability of a ligand to bind to and activate the channel. This is supported by results from Ca 2+ -¯ux and [ 3 H]-ryanodine binding experiments using various diadenosine polyphosphate (Ap n A) compounds (Holden et al, 1996;Morii & Makinose, 1992) where the more phosphates separating the two adenosine moieties, the more eective and potent the compound. 2+ from 10 to 65 mM.…”
Section: +supporting
confidence: 61%
“…As such large dierences in the activity of the adenine nucleotides can be achieved by the removal or addition of a single phosphate group, electrostatic interactions between the phosphates and the amino acid residues in the binding sites may play an important role in determining the ability of a ligand to bind to and activate the channel. This is supported by results from Ca 2+ -¯ux and [ 3 H]-ryanodine binding experiments using various diadenosine polyphosphate (Ap n A) compounds (Holden et al, 1996;Morii & Makinose, 1992) where the more phosphates separating the two adenosine moieties, the more eective and potent the compound. 2+ from 10 to 65 mM.…”
Section: +supporting
confidence: 61%
“…It has been shown that A p A inhibits ADP-induced platelet aggregation (Zamecnik et al, 1992;Busse et al, 1988;Harrison et al, 1975) and influences smooth muscle tone of isolated rabbit arteries (Pohl et al, 1987;Luthje & Ogilvie, 1987). In addition, Ap4A has been shown to increase basal secretion of catecholamines from isolated chromaffin cells (Casto et al, 1990), elicit excitation of the rat nodose ganglion (Marchenko et al, 1988), and induce intracellular calcium flux (Casto et al, 1992;Morii & Makinose, 1992). We have shown that binding of A p d to mouse brain synaptosomes is saturable and highly specific.…”
mentioning
confidence: 96%
“…In higher eukaryotes, Ap n A appear also to be intracellular mediators of certain extracellular stimuli; they respond to glucose in pancreatic ␤-cells (10). Ap n A may also regulate ATP-sensitive K ϩ channels in ␤-cells and cardiac muscle (11)(12)(13) and intracellular ryanodine-binding Ca 2ϩ -release channels in cardiac and skeletal muscle, and in the brain (14,15). Finally, extracellular Ap 5 A and Ap 6 A have also been identified as neurotransmitters (2) and vasomodulators (16,17).…”
mentioning
confidence: 99%